PO.5.118 Functional multiparametric mri to assess renal involvement in SLE. (27th September 2022) - Haase, I; Kernder, A; Ljimani, A; Chehab, G; Mucke, J; Düsing, C; Fischer-Betz, R; Sewerin, P; Sander, O; Antoch, G; Schneider, M
Abstract : Introduction and Purpose: Renal involvement impairs the outcome of systemic lupus erythematosus (SLE). Renal biopsy is the gold standard of confirming the diagnosis of lupus nephritis but the assessment of reversibility and follow-up remain a challenge. In particular there is a need for non-invasive methods in situations of an unfavourable benefit/risk ratio (e.g., risk of bleeding, suspected minor changes). Non-contrast functional multiparametric MRI (mpMRI) can provide information on morphology, perfusion, and microstructure. Initial studies show changes in renal pathologies. 1 Renal T1 mapping shows changes in acute kidney injury, but it also correlates with fibrosis and loss of function in chronic kidney disease. 2, 3 The aim of this pilot study was to investigate the feasibility of mpMRI including T1 mapping, the latter not yet described in lupus nephritis. Methods: The renal mpMRI protocol applied in this study includes techniques for non-contrast assessment of tissue perfusion (Arterial Spin Labeling; ASL), tissue oxygenation (Blood Oxygenation Level Dependent; BOLD) and tissue integrity and structure assessment techniques such as T1 mapping, the apparent diffusion coefficient (ADC) and fractional anisotropy (FA). We compared the renal mpMRI in three affected SLE patients with different states of renal involvement (active vs. former vs. no renal involvement): 1. Active LN IV/V (Creatinine 0.69 mg/dl, Proteinuria 3.2 g/g Creatinine, Erythrocyturia 201/µl, 70% dysmorphic erythrocytes). 2. Former LN III (2011) (2021: Creatinine 1.44 mg/dl, Proteinuria 0.26 g/g Creatinine, Erythrocyturia 26/µl). 3. SLE without evidence of renal involvement (Creatinine 0.77 mg/dl, Proteinuria <0.15 g/g Creatinine, Erythrocyturia 25/µl). Results: Case 1 (active LN IV/V) shows a decrease in ADC as a possible sign of edema and a reduction in renal blood flow. Tissue oxygenation, as a possible correlate of active inflammation, is clearly increased. Cortical T1 times are strongly increased, which might be caused by edema. Case 2 (former LN III) shows reduced medullary FA as an indication of (chronic) tubular damage. Renal oxygenation is normal. Renal blood flow and ADC are slightly decreased, while T1 times are slightly increased, which might be expression of a fibrotic process. Case 3 (control) also shows reduced medullary FA, while other parameters are normal ( figure 1 ). Conclusions: Multiparametric renal MRI of patients with LN shows differences in renal involvement and between acute and chronic manifestation. First examples of T1 mapping suggest applicability to this condition. Further studies are planned to establish this promising method in diagnosis, prognosis assessment and therapy control of renal involvement in SLE. References: doi: 10.1016/j.mri.2015.06.019. Epub 2015 Jun 25. PMID: 26119419. doi: 10.1007/s00330-017-4943-4. Epub 2017 Jul 14. PMID: 28710580. doi: 10.1093/ndt/gfz129. PMID: 31257440; PMCID: PMC7282828.